An Integrated Enzymatic Approach to Produce Pentyl Xylosides and Glucose/Xylose Laurate Esters From Wheat Bran - Jocquel, Chloé; Muzard, Murielle; Plantier-Royon, Richard; Rémond, Caroline (Frontiers in Bioengineering and Biotechnology, 2021)
Alkyl glycosides and sugars esters are non-ionic surfactants of interest for various applications (cosmetics, food, detergency, …). In the present study, xylans and cellulose from wheat bran were enzymatically converted into pentyl xylosides and glucose and xylose laurate monoesters. Transglycosylation reaction catalyzed by the commercial enzymatic cocktail Cellic Ctec2 in the presence of pentanol led to the synthesis of pentyl -D-xylosides from DP1 to 3 with an overall yield of 520 mg / g of xylans present in wheat bran. Enzymatic hydrolysis of wheat bran with Cellic Ctec2 and subsequent acylation of the recovered D-glucose and D-xylose catalyzed by the commercial lipase N435 in the presence of lauric acid or methyl laurate produced one D-glucose laurate monoester and one D-xylose laurate monoester. An integrated approach combining transglycosylation and (trans)esterification reactions was successfully developed to produce both pentyl xylosides and D-glucose and D-xylose laurate esters from the same batch of wheat bran.